A grounded theory approach to investigate the perceived soundscape of open-plan offices. (February 2018) - Acun, Volkan; Yilmazer, Semiha
Abstract: This paper presents the findings of a user focused soundscape survey, that took place in a visual task based and a computational task based open-plan office spaces. Aim of this study was to conduct a grounded theory survey which captures individuals' subjective response to the soundscape and creating a conceptual framework in the end. In order to achieve this goal, acoustical environment and sound sources were identified. In-situ measurements of sound levels ( LAeq ) and simulations, prepared by Odeon Room Acoustics Software 13.10 Combined, were used to explore the acoustical environment of the office spaces. Grounded Theory was used as the main research method to create a conceptual soundscape framework, and to reveal employees perception of the soundscape of their work environment. As part of grounded theory, semi-structured interviews were conducted with forty-nine employees from both types of offices. The results showed how the task at hand were affected by the sound environment and employees' characteristics. Sound that were not expected or out of context and those that interfere with the concentration demanding tasks caused a negative interpretation of the soundscape. Due to this, employees' adopted coping methods such as, accepting and habituating, intervening to the sound source, or putting on headphones to isolate themselves from the soundscape. It was discovered during the interviews that employees were concerned with silence as much as they were concerned with the noise. Employees expressed that the sound of keyboard and mouse means that they are working at that moment, there are other people around, and they are not working alone, or not working overtime.